Improving Students’ Writing Skills through Writing Workshop: An Action Research (NOBEL: Journal of Literature and Language Teaching, 2022)
The present study aims at finding out how writing workshop improves the students’ writing, particularly their grammatical and mechanical writing skills. The approach, which consisted of three stages starting from mini-lesson, writing, and sharing, was implemented on 28 students who took the Writing II Course. An observation checklist, test, field notes, and questionnaire were administered to collect the data in this collaborative action research. The findings of the study revealed that the implementation of the writing workshop was successful in reaching the objective after the revision and the modification were made to conduct cycle two. After reshuffling the format of the workshop to be mini-lesson, sharing, and independent writing, improvements were seen in students’ writing. Furthermore, most of the students stated that working in a group allows them to learn more about using proper grammar and punctuation in writing. Related to the limitations of the study, recommendations for implementing a writing workshop for future research are discussed.